The MACBETH approach to evaluate strategies for the conservation of architectural heritage - Stellacci, S.; Rato, V.; Laureano, R. (MCDM Methods for Business and Management, 2020)
The critical appraisal of alternative strategies in conservation projects of historical buildings is often a complex task that requires balancing a variety of conflicting criteria related to multiple stakeholders and requirements. The main purpose of this study is to make the case for the use of multi-criteria decision analysis in supporting a consistent and transparent, inter-disciplinary decision-making process, using the case study of repair and strengthening techniques of timber frame walls. The MACBETH approach is particularly suitable in this field of research since the judgment procedures allow for an appropriate analysis of intangible values such as the ones at stake in architectural heritage.